PENGARUH PENGAWASAN, KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP DISIPLIN KERJA (STUDI KASUS PADA KARYAWAN PT ELNUSA PETROFIN) PEKANBARU - Lentina Hutabarat; Zulfadil Zulfadil; Prima Andreas Siregar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of supervision, compensation, and organizational culture on employee discipline of PT Elnusa Petrofin Branch Pekanbaru. As for the population in this study are all employees of PT Elnusa Petrofin Branch Pekanbaru as many as 223 people. This research use cluster random sampling method with slovin formula then selected 143 people sample. The method of analysis used in this research is quantitative descriptive method, simultaneous and partial analysis (multiple linear regression analysis with the help of SPSS program version 23.00) From the test result that has been done, simultaneous test (F test) shows that Supervision, Compensation, and Organizational Culture simultaneously have a significant effect on employee work discipline, whilw partial (t test) indicate that Supervision and Compensation partially significant to work discipline employees. The magnitude of the effect of the R2 by these three variables together on the dependent variable 46,1% while the remaining 53,9% is effect by other variables. Companies should pay more attention to discipline the employee to work with the maximum as leaders must have the courage to act decisively to apply penalties to subordinates who violate the rules. If there are employees who do not comply with work rules, the company reserves the right to give strict punishment for those employees. Sanctions here could be a suspension or dismissal of employees when the employee is no longer care for work discipline and reprimand from the boss.Keywords : Supervision, Compensation, Organizational culture, and Discipline Work